Muhammadiyah Microfinance Institutions After the Enactment of Law No.1 of 2013 Concerning Microfinance Institutions - Darojatun Andara; M Hafidz Sidqi A (Gerechtiheid Law Journal, 2021)
Law Number 1 of 2013 concerning Microfinance Institutions (MFIs) In the transitional provisions of Article 39 Paragraphs (1) and (2) of Law No.1 of 2013 concerning MFIs. it is stated that Baitut Tamwil Muhammadiyah (BTM) is a Microfinance Institution and is required to become an MFI by registering with the OJK. While the Microfinance Institutions owned by Muhammadiyah are not all named Baitut Tamwil Muhammadiyah (BTM) and the legal entity used is a Cooperative and is in the form of KSPPS whose legal basis is Law Number 25 of 1992 concerning Cooperatives and Permenkop and UKM Number 02/2017 concerning Amendments to Permenkop Number 15/2015 concerning Savings and Loans Business and Sharia Financing by Cooperatives.This study aims (1) to find out how the position of the Muhammadiyah Microfinance Institution in the 2 (two) laws and regulations governing the form of cooperatives and (2) to determine the factors that influence the selection of the form of business entity. This research is a normative juridical research. So this research was conducted in libraries by examining primary and secondary materials, as well as interviews with resource persons, in order to support or become additional secondary materials.The results of this study indicate (1) that the position of BTM and LKM Muhammadiyah is legally valid as long as it is subject to the Cooperative Law. Because BTM and LKM Muhammadiyah chose the Cooperative Law and the KSPPS Cooperative Government as their legal basis. However, the obligation to register with the OJK as an LKMS under the MFI Law remains in effect until the rules are revoked or revised. (2) Factors influencing the selection of a Muhammadiyah MFI business entity, either LKMS or KSPPS.